Application of Photovoice in Qualitative Researches - Nikbakht Nasrabadi, Alireza; Najafi, Fatemeh; Mardanian-Dehkordi, Leila (Advances in Nursing & Midwifery, 2019)
The concept of photovoice was at first invented in 1997, it is a visual participatory tool to collect data in qualitative studies that was widely used in different countries and various health issues [1, 2]. It employs contributors to take photograph of a subject of concern, critically reflecting on the subject, and yields solutions for these problems [3]. In this method of data collection, cameras are provided to contributors in order to share their facts, stories, and target commonplace issues in their lives [4]. It’s also been used to express needs, history, culture, problems and desires [5]. Photovoice's method is based on three theoretical foundations that overlap one another: documentary photography, feminist theory, and the critical awareness theory of Paulo Freire [2]. Photovoice has three main objectives: 1. encouraging and empowering people to record and give feedback on strengths and problems in their societies; 2. Promoting critical knowledge on important issues through group discussions on pictures and 3. Providing easier access to policy makers to change [1]. This process consists of several components. The researchers first set objective matter and select participants that are relevant to the object matter. At the beginning, participants will be provided with brief tutorials on photography skills, photovoice ethics and safety. After that photos which are provided by participants should be discussed through interviews, telling stories and big and small discussion groups which researchers evaluate the reasons of choosing their own images and feelings by using an integrated structures. The researchers then analyze the content and extract the relevant codes. Finally photos will published in magazines or websites if necessary [6, 7]. Photovoice has positive results on individual and community health, developing trust, making a sense of ownership, social skill development, increasing individual self-efficacy, learning together, building community capacities, creating community change and balancing research and practice [2, 6, 7]. The photovoice limitation is related to the inability of children to respond accurately to photos and how photos exhibit their experiences from the topic. To manage this limitation, researchers also used an evidence-based approach as complementary method [7]. Photovoice is proposed as one of the methods aimed at collecting data in qualitative studies to enrich the results of studies and provide an accurate understanding of the topic from the participants’ perspectives.